HEPATOPROTECTIVE EFFECT OF BAY LEAVES CRUDE EXTRACT ON PRIMARY CULTURED RAT HEPATOCYTES - Ayoub, Nahla A.; Hashim, Amani N.; Hussein, Sahar A.; Hegazi, Nesrine M.; Hassanein, Heba M.; Nawwar, Mahmoud A. (European Scientific Journal, ESJ, 2013)
The crude extract of bay leaves (Laurus nobilis) grown in Egypt, was tested for its hepatoprotective activity on primary cultured rat hepatocytes against paracetamol toxicity. The Neutral Red Assay was used to assess the hepatotoxicity of the extract and was applied with a broad range of concentrations (125-1000 μg/ml) on monolayer of rat hepatocytes. It revealed that the extract exerts no toxic effect on the monolayer hepatocytes. For the evaluation of the hepatoprotective effect; different concentrations were prepared, starting from 12.5 μg/mL and increasing concentration in ascending order by dissolving in DMSO (1% maximum concentration). For each concentration, three replicates were carried out, in addition to controls which were: cell control (cells only), negative control (cells + paracetamol) and positive control (reference) (cells + sylimarin + paracetamol). 50% mortality of the hepatocytes (IC50) was determined using Neutral Red Assay. L. nobilis extract showed hepatoprotective activity against paracetamol toxic effect at concentration of 40 μg/ ml. The constitutive flavonoids of L. nobilis leaves were extensively studied and led to the separation and identification of 14 compounds, 10 of which have not been previously identified in L. nobilis and were identified using chemical, conventional and advanced spectral techniques.